Cultural Heritage Tourism Activities in Pashupatinath Area (Journal of Tourism and Himalayan Adventures, 2019)
Pashupatinath area, as a cultural heritage site, commands immense attractions and the interests of the religious and pilgrimage tourists. It is one of the national identities and pride, enlisted in the world heritage site. As a symbol of national pride, this area showcases enormous potential for multifaceted growth, however, there are various activities and structural development remained to be done. Lack of properly developed tourism guidelines and implementations mechanism seem obvious to discerning eyes. This study tries to explore on the significance and importance of Pashupatinath heritage site and its vicinity in terms of tourism. In this regard, this study tries to observe and highlight some of the recent activities geared to uplift the hitherto less focused areas with a hope to attract some concerned stakeholders’ and authorities’ due attention.